ORGANIZATION OF INDEPENDENT WORK OF COMPUTER SCIENCE STUDENTS USING EXISTING WEB APPLICATIONS - Головач, Йожеф (SWorldJournal, 2025)
The article considers the problems associated with the organization of independent work of computer science students. As is known, the most useful are tasks that have a practical focus, that is, have real, practical content. But with limited time for inde